Numerical investigation of bolted rock joints under varying normal stress and joint roughness coefficient conditions - Wang, Zhiyong; Liao, Liyun; Guo, Shiyi; Zheng, Hanfang; Wu, Xuezhen (Frontiers in Earth Science, 2024)
Rock masses are formed through long-term, complex geological processes, and the presence of joints significantly reduces their strength and increases their deformation. Rock bolts effectively enhance the strength and stability of rock masses and are extensively utilized for reinforcement. According to field investigations, a significant portion of the damage to bolted rock masses stems from shear deformation at joint surfaces. Moreover, roughness affects friction and surface contact, thus influencing the shear behavior between rock and rock bolts. This study considers two crucial factors affecting the shear characteristics of bolted rock joints: joint surface roughness and normal stress. Using the Particle Flow Code discrete element numerical method, the Barton standard joint profile lines were input to establish numerical models of both unbolted and bolted rock joints for direct shear tests. Results reveal that the peak shear stress and stiffness of both unbolted and bolted rock joints increase with rising normal stress and joint roughness coefficient. The peak shear stress and stiffness of bolted rock joints are notably higher than those of unbolted ones, with a maximum increase of 17.5%. Crack development in bolted rock joints occurs in stages of rapid, slow, and stable development, whereas no distinct slow development stage is observed in unbolted rock joints. Additionally, micro cracks in both unbolted and bolted rock joints are primarily tensile cracks, originating around the joint surface and extending outward with increasing shear displacement. These findings offer valuable insights into the microscopic shear mechanics of bolted rock joints and provide practical references for engineering design and applications in rock reinforcement projects.